The sound of complaints - Mauchand, Maël; Pell, Marc D. (Frontiers in Communication, 2025)
Complaining is a social act in which a speaker often verbally conveys feelings of suffering to gain empathy from listeners. The present study investigated the acoustic profile of complaints to identify which prosodic features are used in this context and to explore differences in their cultural expression in two variants of French. A stimulus set composed of 336 complaints and 336 prosodically neutral utterances produced by two cultural groups, French and Québécois (French-Canadian), was analyzed along 15 acoustic parameters. Utterances were also judged by listeners to determine whether complaints were perceptually associated with particular emotional characteristics. Relative to neutral statements, complaints displayed increases in fundamental frequency (mean, variability, and range), loudness, and high-frequency energy, and several rhythmic modulations. Complaints were also characterized by systematic changes in parameters related to voice quality and increased vocal control (decreased shimmer, increased harmonics-to-noise ratio), which could exemplify the speaker’s strategic use of emotive cues. Perceptually, complaining voices were most associated with sadness, anger, and surprise. Complaints produced by French and Québécois speakers demonstrated shared central tendencies but also differed both acoustically and perceptually. Our results provide new insights into the acoustic and perceptual profiles of emotive “complaining” speech patterns meant to elicit empathy in social interactions.